Liberalism, Law and Social Rights: The Charter of Rights and Freedoms in the Era of Welfare State Restructuring - Karimi, Sirvan (International Journal of Law and Public Policy (IJLAPP), 2022)
Despite expanding the boundary of formal equality, the Charter of Rights and Freedoms is conducive to rationalizing liberalism's conception of the role of the state. Contrary to the hasty expectation of social rights advocates who hoped that they can utilize the Charter to advance social rights in Canada, the Charter has in fact been interpreted by the courts in a manner that justifies the subordination of the social rights to the vicissitudes in the economic sphere, which has historically been ingrained as an overriding tenet of liberalism. In line with a long-held liberal principle that the real threat to individual liberty emanates from the state, not private property relations which are indeed the basis for socio-economic inequalities, the Charter interpretations by the courts have, in fact, reinforced a legal rationalization for the neoliberal-motivated forces of welfare state retrenchment which are reflected in the courts’ refusal from imposing any positive obligation on the state to provide the basic means of subsistence for citizens as a matter of right. Thus, judicial interpretation of the Charter reflects and reinforces the nineteenth-century liberal tenet that the judiciary can restrain but cannot compel the state to take positive actions.